Eohypsibiidae (Eutardigrada, Tardigrada) from the Faroe Islands with the description of a new genus containing three new species - Trygvadóttir, Birna Vár; Kristensen, Reinhardt Møbjerg (Zootaxa, 2011)
A diverse eutardigrade fauna of the family Eohypsibiidae Bertolani & Kristensen, 1987 was collected on the Faroe Islands. The first record of Bertolanius weglarskae (Dastych, 1972) and new records of Eohypsibius nadjae Kristensen, 1982 are documented. The new genus Austeruseus is established and three new species, Austeruseus faeroensis, nov. sp., A. balduri nov. sp. and A. rokuri nov. sp. are described. The genus differentiates from the genera Bertolanius and Eohypsibius in the buccal tube. The apophyses for the insertion of stylet muscles are (two or six) lateral hooks and the entire length of the mouth and buccal tube are straight in Austeruseus, while Bertolanius and Eohypsibius have the apophyses for the insertion of stylet muscles as crests with ventral and dorsal hooks, and the mouth and buccal tube are flared or trumpet shaped. With five species the Faroese tardigrade fauna is the richest in the world with regard to the family Eohypsibiidae. The genus Austeruseus is primarily found in mosses at high mountain biotopes, and the new genus may be a glacial relic.